2013
DOI: 10.1208/s12248-013-9477-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Magnitude and Duration of Target Inhibition Following Antibody Therapy: Implications in Drug Discovery and Development

Abstract: Abstract. Antibodies or antibody-related fusion proteins binding to soluble antigens in plasma form an important subclass of approved therapeutics. Pharmaceutical companies are constantly trying to accelerate the pace of drug discovery and development of these antibodies and identify superior candidates in face of significant attrition rates. Understanding the interplay between drug-and targetrelated factors on magnitude and duration of target inhibition is imperative for successful advancement of these therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Chimalakonda et al 13 investigated the percentage inhibition of the receptor and confirmed that decreasing K D by increasing k on resulted in lowering the minimum concentration of the receptor and improving the duration of receptor inhibition. However, the maximum duration of receptor inhibition was found to be fixed for a particular antibody and dose, regardless of its binding rate.…”
Section: Parameters That Affect Potencymentioning
confidence: 94%
See 1 more Smart Citation
“…Chimalakonda et al 13 investigated the percentage inhibition of the receptor and confirmed that decreasing K D by increasing k on resulted in lowering the minimum concentration of the receptor and improving the duration of receptor inhibition. However, the maximum duration of receptor inhibition was found to be fixed for a particular antibody and dose, regardless of its binding rate.…”
Section: Parameters That Affect Potencymentioning
confidence: 94%
“…Chimalakonda et al . investigated the percentage inhibition of the receptor and confirmed that decreasing K D by increasing kon resulted in lowering the minimum concentration of the receptor and improving the duration of receptor inhibition.…”
Section: One‐compartment Modelmentioning
confidence: 94%
“…17 Modelers have sought to develop rules of thumb for predicting how changing the drug properties or dosing regimen will impact measures of drug activity, such as maximum target inhibition or duration of effect of a single dose. [18][19][20][21][22] Thus far, the existing metrics and analyses apply only to single-dose scenarios, which is of limited value because most mAbs are dosed repeatedly in the clinic.…”
Section: What Question Did This Study Address?mentioning
confidence: 99%
“…This translates to a twofold difference in dosing (as measured by mg/kg) to achieve similar efficacies in mice and humans. This in turn suggests a required antigenic potency (EC 50 ) below 100 pM (<15 ng/mL [65,66]. It will also be important to show that there is no antibody-dependent enhancement [67].…”
Section: Mabs Optimizationmentioning
confidence: 98%